Oblong turtles hybridise with an introduced congener and display a size-heterozygosity relationship - Brenton von Takach; Anthony Santoro; April L. Sturm; Kailah M. Thorn; Stephen J. Beatty (Conservation Genetics, 2026)
Freshwater turtles are among the most imperilled vertebrate groups globally, facing compounding threats from habitat loss, climate change, and invasive species. We conducted the first comprehensive range-wide genomic assessment of the oblong turtle ( Chelodina oblonga ; Indigenous Noongar: Yaakan and Booyi), a species endemic to the rapidly drying biodiversity hotspot of southwestern Australia. To evaluate individual and population genomic structure and diversity, we used reduced representation sequencing to genotype 466 individuals from 60 sites across the species’ distribution. Our results reveal the first evidence of hybridisation in the wild between C. oblonga and the introduced eastern snake-necked turtle ( C. longicollis ). The detection of putative backcrossed individuals implies that introgression may be actively occurring. Population structure analyses of C. oblonga identified a distinct latitudinal gradient with hierarchical substructure, while genomic diversity was lowest at the northern and southeastern range extremities, consistent with range-edge effects. We also identified a significant positive relationship between linear carapace length and individual heterozygosity. Larger individuals exhibited higher diversity than smaller individuals, suggestive of a heterozygosity-fitness correlation. These findings provide critical genomic data for the oblong turtle as well as highlight a need to monitor the impacts of invasive species in increasingly modified aquatic ecosystems.